2022
DOI: 10.1186/s40249-022-01008-5
|View full text |Cite
|
Sign up to set email alerts
|

Re-emerging threat of Trypanosoma cruzi vector transmission in El Salvador, update from 2018 to 2020

Abstract: Background Since the late twentieth century, Chagas disease gained global attention to suppress the vector burden as a main control strategy in endemic countries. In Central America, multi-national initiative successfully achieved significant reduction in the estimated disease prevalence as well as elimination of the region’s principal vector species at the time in 2012. While the last decade has witnessed significant changes in ecosystem—such as urbanization and replacement of the main vector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…As clustering of disease cases frequently occurs with T. cruzi infection, results of this study support prior evidence that ongoing vector-borne transmission is still occurring and a portion of pediatric cases in this region of El Salvador could possibly be contributed to congenital infection. A recent publication of T. dimidiata dispersion found a 10% overall T. cruzi infection rate within the disease vector and an elevated infection rate in the departments of Ahuachapan and Sonsonate [36]. The study further found >34% of surveyed houses had triatomine domiciliation.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…As clustering of disease cases frequently occurs with T. cruzi infection, results of this study support prior evidence that ongoing vector-borne transmission is still occurring and a portion of pediatric cases in this region of El Salvador could possibly be contributed to congenital infection. A recent publication of T. dimidiata dispersion found a 10% overall T. cruzi infection rate within the disease vector and an elevated infection rate in the departments of Ahuachapan and Sonsonate [36]. The study further found >34% of surveyed houses had triatomine domiciliation.…”
Section: Discussionmentioning
confidence: 66%
“…The study further found >34% of surveyed houses had triatomine domiciliation. Adobe houses were most highly colonized by triatomines followed by mud and brick [36]. Substandard living conditions and socioeconomic limitations in certain parts of the western departments create risk for exposure to infected insects.…”
Section: Discussionmentioning
confidence: 99%
“…The connectives present a yellow–orange coloration and with a very extensive characteristic dark central spot. Previous reports have shown the existence of species similar to T. dimidiata (Dorn et al, 2018; Lima‐Cordón et al, 2019), but due to the characteristics of the pronotum, legs and abdomen, the specimen corresponds to T. dimidiata ; this group of insects was mainly associated with sylvatics environments; however, it has expanded its habitat to domestic areas, through adaptation processes to environmental changes, increasing its interaction with humans (Dorn et al, 2007; Rodríguez et al, 2022). In addition, due to the position and magnitude of the central spots characterized by the Feret diameters; observed in the specimen, indicate its correspondence to a specimen of T. dimidiata of haplogroup 2 (Figure 2a), these spots are significantly different between T. dimidata haplogroups (Cruz et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Between 2018 and 2020, a study in El Salvador, covering 107 households, revealed a 34.4% infection rate among approximately 1500 examined triatomines, vectors of the Chagas disease, and no less than 10% of them having the potential to transmit T. cruzi to humans [7]. In 2018, a surveillance study in western El Salvador found that the seropositivity rate for pediatric Chagas disease in the Sonsonate Department was 2.3%, surpassing the reported national adult rate of 1.7% [8].…”
Section: Introductionmentioning
confidence: 99%